3D Printing Applications for Radiology: An Overview - Haleem, Abid; Javaid, Mohd; Suman, Rajiv; Singh, Ravi Pratap (Indian Journal of Radiology and Imaging, 2021)
Three-dimensional (3D) printing technologies are part of additive manufacturing processes and are used to manufacture a 3D physical model from a digital computer-aided design model as per the required shape and size. These technologies are now used for advanced radiology applications by providing all information through 3D physical model. It provides innovation in radiology for clinical applications, treatment planning, procedural simulation, medical and patient education. Radiological advancements have been made in diagnosis and communication through medical digital imaging techniques like computed tomography, magnetic resonance imaging. These images are converted into Digital Imaging and Communications in Medicine in Standard Triangulate Language file format, easily printable in 3D printing technologies. This 3D model provides in-depth information about pathologic and anatomic states. It is useful to create new opportunities related to patient care. This article discusses the potential of 3D printing technology in radiology. The steps involved in 3D printing for radiology are discussed diagrammatically, and finally identified 12 significant applications of 3D printing technology for radiology with a brief description. A radiologist can incorporate this technology to fulfil different challenges such as training, planning, guidelines, and better communications.
Keywords: 3D printing; 3D printing applications; imaging; medical; radiology